Hodgkin’s disease presenting with pyrexia of unknown origin - Branco, Vitor; Salvador, Maria João; Silva, Mário Rui; Martins, Paulo; Carvalho, Armando; Almiro, Eurico; Porto, Armando (Portuguese Journal Internal Medicine, 1998)
ln Hodgkin's disease, the anatomical extension of the disease and the histological sub type are the major determinants of the forms of disease presentation. Frequently, clinical manifestations have low specificity and it is difficult to suspect tbe diagnosis. A clinical case is reported of abdominal Hodgkin's disease of tbe lympbocyte depleted type, that presented initially with pyrexia of unknown origin, followed by successive clinical and laboratory abnormalities, which, despite their severity, were not specific enough to elicit an immediate diagnosis. A few of the less frequent forms of presentation of Hodgkin's disease are discussed, stressing the importance of being alert to the less typical manifestations of this disease.